The Multi Donor Fund for Aceh and Nias : A Framework for Reconstruction through Effective Partnerships - MDF-JRF Secretariat (World Bank, Jakarta, 2014)
The Multi Donor Fund for Aceh and Nias (MDF) and the Java Reconstruction Fund (JRF) have played significant roles in the remarkable recovery of Aceh, Nias and Java, following some of the worst disasters in Indonesia in recent years. The MDF and the JRF, which is patterned after it, are each considered a highly successful model for post-disaster reconstruction. This paper presents experiences from the implementation of the MDF, and documents key lessons on its strategic framework and design which contributed to the MDF's success in supporting the government of Indonesia's reconstruction agenda.